Menggugat Prinsip Non-Interference ASEAN : Dari Idealisme ke Pragmatisme Politik? - Husnul Atiyah (Institut Kewarganegaraan Indonesia, 2024)
Several acts of violence that occurred at the national and international levels received attention from various groups. The conflict between Russia and Ukraine and the Myanmar issue involving the military junta regime have become prominent in recent years. The conflict between Russia and Ukraine, even though it occurred in Eastern Europe, has the potential to have an impact on global security, and is even said to trigger a world war. The violence case in Myanmar, while it occurs on a national (domestic) level, the impacts, especially the violence and abuses of human rights, are extraordinary and are of serious international concern. Both cases sparked criticism from various groups, including the United Nations (UN) at the international level and ASEAN at the regional level. This article discusses ASEAN members’ stance on the two violent incidents that occurred by linking it to the principle of noninterference, one of the principles that are very “ASEAN”. Through literature study, this paper finds that ASEAN’s attitude towards the two cases above is not singular. Each member’s attitude of this Southeast Asian regional organization is different, especially in the case of the Russia and Ukraine conflict. In the case of Myanmar, the attitude shown is also not firm. The description of this attitude is closely related to how they interpret the principle of non-interference, which tends to be political and pragmatic in practice, depending on the interests of their respective countries.